2014
DOI: 10.1136/annrheumdis-2014-eular.5848
|View full text |Cite
|
Sign up to set email alerts
|

THU0350 Ultrasonographic Study of the Piriformis Muscle and Sonographic Features of the Piriformis Syndrome in Chronic Low Back Pain

Abstract: Background Piriformis Syndrome is thought to account for about 5 to 10 percent of the cases of chronic low back and gluteal pain and could cause debilitating chronic suffering. However as at present there are no specific confirmatory tests, it remains mainly a diagnosis of exclusion. On the other hand musculoskeletal ultrasound is a rapidly developing imaging modality, particularly efficient in the evaluation of lesion in soft tissues. Objectives To study the piriformis muscles by sonography in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our study found that the mean PM thickness in PS patients was significantly higher compared to the healthy subjects (1.16 ± 0.13 and 0.89 ± 0.11, respectively, p = 0.00). These results are similar to those of Zhang et al ( 10 ), Todorov et al ( 14 ), and Wu et al ( 7 ) who found increased mean PM thickness in PS subjects. Although the study by Siddiq et al had the same results, the PM thickness difference in those study was not statistically significant ( 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study found that the mean PM thickness in PS patients was significantly higher compared to the healthy subjects (1.16 ± 0.13 and 0.89 ± 0.11, respectively, p = 0.00). These results are similar to those of Zhang et al ( 10 ), Todorov et al ( 14 ), and Wu et al ( 7 ) who found increased mean PM thickness in PS subjects. Although the study by Siddiq et al had the same results, the PM thickness difference in those study was not statistically significant ( 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…Apart from the significance of PM thickness in US, previous studies have also shown a wide variation in PM thickness in their study without detailed US methods. In the study of Todorov et al ( 14 ) the anterior-posterior PM thicknesses of PS were 5.8 to 11.55 mm (males) and 4.4 to 9.6 mm (females), whereas the anterior-posterior PM of PS was 13.55 ± 3.66 mm (affected) in the study of Siddiq et al ( 15 ). Those variations might be caused by the subject's different activities.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations